Role of firm features in determining macroeconomic exposure of firm volatility, risk-return trade off, asymmetric and leverage effect - Butt, Muhammad Saqib Bashir (2023)
This thesis aims at investigating the role of five firm features namely; firm age (youngest and oldest age), firm size (smallest and largest size), firm trading nature (exporting and non-exporting), firm nature of business (financial and non-financial) and sectoral location of the firm in determining the macroeconomic exposure (i.e., exchange rate, treasury yield spread, oil prices, and market return) of firm stock returns volatility, risk-return trade-off, and asymmetric and leverage effect. This study employs three Generalized Autoregressive Conditional Heteroscedasticity Models such as (i) GARCH (1,1) model to determine the linkages between the macroeconomic factors and the firm stock returns volatility; (ii) GARCH in Mean model to capture the risk-return trade-off; and (iii) Exponential GARCH model to test the asymmetric and leverage effect at the firm level concerning the five firm features. The study spans from January 3, 2000, to March 31, 2022, and 608 firms listed on the New York Stock Exchange are examined. The results indicated the significant role of firm features. The following are the highlights of the results. First, the market return emerged as the leading factor affecting the firm stock returns volatility significantly, followed by treasury yield spread, oil prices, and exchange rate. Further, the impact of macroeconomic factors on firm stock returns volatility is heterogeneous depending on the firm features. Second, the positive risk-return relationship is dependent on the firm features. Third, asymmetric and leverage effect varies with respect to the firm features. Findings of this thesis are helpful for the (i) investors to achieve optimal portfolio diversification; (ii) the firm managers to improve their risk management techniques; and (iii) the government to devise effective policies. This study is limited to one developed financial market, hence, future studies can be extended to the other financial markets.